The Myth of the 50-Minute Epiphany: #MeToo and Implications for Teaching - Russell, Emily; Kline, Nolan; McClure, Amy; Schoen, Steven; Chick, Nancy (Teaching and Learning Inquiry, 2023)
Because university campuses are microcosms of broader political and social climates, the increasingly polarized climates outside universities can permeate the classroom, challenging faculty who teach topics characterized by controversy and discomfort. We conducted a lesson study project at a college in the southeastern United States in three first-year courses from different disciplines to examine how the broader tensions of the #MeToo movement emerged and affected a class activity focused on gender. We sought to understand our students’ responses to a moment of discomfort generated by discussions of sexual roles, consent, and assault—issues that are relevant in both this cultural moment and in the lives of many first-year college students. We observed responses ranging from affirmation to resistance in what felt at times like our own failure. Without this collaboration, each of us may have been left with a narrower view of what the students learned and an incomplete sense of our own work. What began as an investigation into students’ transformative learning experiences ended as a transformative experience in our own understanding of the acts of teaching and the complexities of student learning. Click here to read the corresponding ISSOTL blog post.